2022
DOI: 10.1183/13993003.02356-2021
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled seralutinib exhibits potent efficacy in models of pulmonary arterial hypertension

Abstract: BackgroundSignalling through platelet-derived growth factor receptor (PDGFR), colony-stimulating factor 1 receptor (CSF1R) and mast/stem cell growth factor receptor kit (c-KIT) plays a critical role in pulmonary arterial hypertension (PAH). We examined the preclinical efficacy of inhaled seralutinib, a unique small-molecule PDGFR/CSF1R/c-KIT kinase inhibitor in clinical development for PAH, in comparison to a proof-of-concept kinase inhibitor, imatinib.MethodsSeralutinib and imatinib potency and selectivity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…Seralutinib is a PDGFR, CSF1R and c-KIT kinase inhibitor that upregulates BMPRII protein expression. Pre-clinical studies have demonstrated efficacy of inhaled seralutinib in animal models of PAH [ 31 ]. The TORREY study is a phase 2 study of inhaled seralutinib in patients with PAH and FC II and III symptoms [ 32 ].…”
Section: Novel Pathways In Pahmentioning
confidence: 99%
“…Seralutinib is a PDGFR, CSF1R and c-KIT kinase inhibitor that upregulates BMPRII protein expression. Pre-clinical studies have demonstrated efficacy of inhaled seralutinib in animal models of PAH [ 31 ]. The TORREY study is a phase 2 study of inhaled seralutinib in patients with PAH and FC II and III symptoms [ 32 ].…”
Section: Novel Pathways In Pahmentioning
confidence: 99%
“…Two additional PDGFR-related kinases have also been involved in the pathobiology of PAH: the colony stimulating factor 1 receptor (CSF1R) and the tyrosine-protein kinase KIT (c-KIT). CSF1R is expressed on monocytes and macrophages, which secrete PDGF ligands and inflammatory cytokines, thereby promoting inflammation and remodeling of the pulmonary vasculature [ 55 , 56 ]. C-KIT is expressed on endothelial progenitor cells and mast cells, and it has been observed in plexiform lesions from patients with PAH.…”
Section: Pathobiology Of Pahmentioning
confidence: 99%
“…Treatment strategies available to date are aimed at antagonizing the inappropriate vasoconstriction that occurs in PAH and target three different major signaling pathways: (1) the nitric oxide and soluble guanylate cyclase pathway (phosphodiesterase inhibitors [sildenafil, tadalafil] and soluble guanylate cyclase stimulators [riociguat]); (2) the endothelin pathway (endothelin receptor antagonists [ambrisentan, bosentan, macitentan]) [ 12 , 13 ]; and (3) the prostacyclin pathway (prostacyclin analogues [epoprostenol, iloprost, treprostinil] and prostacyclin receptor agonist [selexipag]) [ 3 , 11 , 14 , 86 , 87 ]. Current and upcoming preclinical and clinical research is focused on the development of compounds that directly act in the different molecular pathways associated with the development of PAH to counteract the obstructive vascular remodeling and small vessel loss [ 56 , 88 , 89 ]. Specifically, drugs targeting various pathogenic mechanisms are being developed: bone morphogenetic protein signaling, tyrosine kinase receptors, serotonin metabolism, angiogenesis, extracellular matrix, estrogens or epigenetics [ 51 , 90 , 91 ].…”
Section: New Molecular Compounds Targeting the Altered Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Seralutinib (formerly known as GB002) is an inhaled, nonselective inhibitor of platelet-derived growth factor receptor (PDGFR) -α and -β, as well as colony stimulating factor 1 receptor (CSF1R) and c-KIT. In Sugen-hypoxia and monocrotaline rat models of PAH, seralutinib increased BMPR2 levels and caused reductions in right ventricular systolic pressure, mean pulmonary artery pressure, and pulmonary arteriolar muscularization (Galkin et al, 2022). The TORREY trial (NCT04456998) is a current phase 2 controlled randomized trial evaluating seralutinib on WHO Functional Class II and III PAH patients, with change in pulmonary vascular resistance at 24 weeks as its primary outcome (Frantz et al, 2021).…”
Section: Seralutinib (Gb002)mentioning
confidence: 99%